Influencer Blindness : The Erosion of Trust and Effectiveness in Saturated Digital Marketing - Thakkar, Karan (2025)
This Master’s thesis investigates influencer blindness, referring to declining consumer responsiveness to influencer marketing in saturated digital environments. The study examines the effects of perceived content oversaturation and inauthenticity on consumer disengagement and perceived ineffectiveness of influencer marketing, while exploring platform-specific differences in these relationships. A mixed-methods approach was adopted, combining a quantitative survey of 218 social media users in the Czech Republic with supplementary semi structured interviews involving marketing professionals and content creators. Quantitative data were analysed using regression and mediation analyses, supported by qualitative thematic analysis and pattern matching. The findings reveal that content fatigue and cognitive dissonance significantly mediate the relationship between influencer content characteristics and influencer blindness. Qualitative insights further suggest that platform norms, content formats, and algorithmic dynamics shape variations in audience engagement and perceived effectiveness. The study contributes to understanding the erosion of influencer marketing effectiveness and highlights the importance of platform-sensitive and authenticity-driven strategies.